New High-Yielding Triticale Varieties in Rainfed Areas of Uzbekistan - K. T, Isakov; L. B, Mavlanov; B. S., Kushmatov (American Journal of Biodiversity, 2025)
The article presents data on the study of triticale varieties in rainfed conditions. 6 varieties of triticale with high yield, high drought-heat resistance and productivity were selected. This study investigates the performance of new triticale varieties under rainfed conditions in Uzbekistan, focusing on yield potential, drought resistance, and heat tolerance. Triticale, a hybrid of wheat and rye, offers high ecological plasticity and productivity, yet its application in arid environments remains underexplored. Addressing this knowledge gap, the research evaluates the agronomic and physiological traits of selected triticale varieties to identify high-yielding and resilient candidates. The study employed competitive variety trials conducted over three years (2022–2024) at the Gallaaral experimental station. Twelve triticale varieties, including the Sardor standard, were assessed for plant height, 1000-grain weight, biomass accumulation, and protein coagulation temperature. Statistical analyses revealed significant inter-varietal differences in yield and abiotic stress resistance. P1V15 exhibited the highest average yield of 21.9 c/ha, outperforming the Sardor standard (18.4 c/ha), while P61V49 demonstrated superior biomass accumulation at 144.78 g, indicating robust drought and heat adaptability.